Influence of Climatic Constraints on the Finances of Enterprises: Problems and Ways of Their Solution (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Climatic financial constraints in business activities are enshrined in a number of international documents, above all in the Kyoto Protocol and the Paris Climate Agreements, which are important to obey for ukrainian enterprises, especially for exporters to EU countries. At the same time, in these and others internationaldocuments provided significant financial investments for countries and individual enterprises that introduce modern climatic technologies into production, above all for the production of energy from renewable sources. Therefore, it is important for ukrainian enterprises to take into account the requirements of international climate documents, especially for those that carry out export activities. Ukrainian manufacturers should take into account the fact that, not only financial structures, but also manufacturing companies are beginning to close such projects in developed countries under the pressure of the publicand including the financial risks of investing in the extraction and processing of fossil fuels. More and more pension and insurance funds, which are the largest investors in the world, come out from financing programs for the extraction and processing of fossil fuels, primarily coal, which also should be taken into account for business in Ukraine. According to the Paris Climate Agreements, financial resources are provided by developed countries to the developing countries that are parties to this agreement for the purpose of carrying out activities in the field of climate change mitigation. It is important for the ukrainian state and business to prove to the international community the necessity to allocate mentioned funds for our country because Ukraine, is not in a position to eliminate negative climatic consequences, that is as a result of Russia's covert aggression on the Donbass, which can endanger the environment and the climate ofthe whole of Europe. Business in Ukraine is still not enough realise potential of renewable energy, which is targeted by the policy of the leading EU countries. To a certain extent, this is link with the lack of funds from the state and enterprises for similar activities. We see the way out in the development of appropriate climate applications from Ukrainian enterprises to receive grants from international climatic funds, primarily from the Green Climate Fund.
Keywords: climatic constraints, enterprise, Kyoto Protocol, Paris climate agreement, environmental taxes, European Union, Ukraine, Donbass